Die funksie en boodskap van die "voorwoord" in 1 Korintiërs - Malan, F. S. (Hervormde teologiese studies, 1993)
The function and message of the ‘preface’ in 1 Corinthians Paul’s thanksgiving and confession of faith in 1 Corinthians 1:4-9 fulfil the role of the classical preface to arrest the attention of his audience, to seek their goodwill, and to prepare them for instruction in a delicate matter through insinuation. The Corinthians, who boast of their own excellence and privileges, are confronted with God’s abundant and undeserved grace which will unite them to the Christ as the beginning, the continuation and the end of their whole life.